2015
DOI: 10.3748/wjg.v21.i37.10510
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of deciphering gastric cancer heterogeneity

Abstract: Gastric cancer is in decline in most developed countries; however, it still accounts for a notable fraction of global mortality and morbidity related to cancer. High-throughput methods are rapidly changing our view and understanding of the molecular basis of gastric carcinogenesis. Today, it is widely accepted that the molecular complexity and heterogeneity, both inter- and intra-tumour, of gastric adenocarcinomas present significant obstacles in elucidating specific biomarkers for early detection of the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 201 publications
2
52
0
Order By: Relevance
“…These findings support the role of the DCLK1-based miRNA signature in determining a prognosis for colon cancer patients. We note that a number of groups have demonstrated that DCLK1 expression can predict survival in colon cancer [9, 35]. Although we found similar significant results using DCLK1 gene expression data from the TCGA colon cancer RNA-seq dataset (Figure 7), the DCLK1-based miRNA signature was able to stratify risk with much greater efficiency.…”
Section: Discussionsupporting
confidence: 76%
“…These findings support the role of the DCLK1-based miRNA signature in determining a prognosis for colon cancer patients. We note that a number of groups have demonstrated that DCLK1 expression can predict survival in colon cancer [9, 35]. Although we found similar significant results using DCLK1 gene expression data from the TCGA colon cancer RNA-seq dataset (Figure 7), the DCLK1-based miRNA signature was able to stratify risk with much greater efficiency.…”
Section: Discussionsupporting
confidence: 76%
“…GC develops as a biologically heterogeneous disease involving multiple genetic and epigenetic alterations [9, 13, 15, 41]. Aberrant gene expression profiles have been associated with GC progression, prognosis and pathogenesis [9, 13, 15, 41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant gene expression profiles have been associated with GC progression, prognosis and pathogenesis [9, 13, 15, 41, 42]. In the present study, gene expression microarray was applied to screen differentially expressed genes in GC tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecularly-targeted therapy has drawn broad attention recently [8-14]. Identification of novel oncotarget proteins is important for GC diagnosis and treatment [8-11]. …”
Section: Introductionmentioning
confidence: 99%